Modified Distribution Transformer for Enhancing Power Quality in Distribution Systems - Preetha P.K.; P.S. Chandramohanan Nair (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
The percentage of non-linear loads in the power distribution sector is increasing day by day. Harmonics injected by these non-linear loads circulate in the delta windings of the conventional distribution transformer thereby increasing the temperature and losses. This reduces the efficiency and life of the transformers. In a modified distribution transformer configuration proposed recently, called star-star-delta_utilized configuration (YYD_utilized), the harmonics circulating in the delta winding was utilized and the drainage power thus recovered was used to power auxiliary loads. This paper presents the experimental studies conducted on YYD_utilized distribution transformer. When compared to conventional star-star, delta-star and star-star-delta transformers, the new configuration of YYD_utilized transformer has shown considerable improvement in transformer efficiency.  The results obtained show that when the power from the circulating harmonics is recovered and utilized, it not only improves transformer efficiency but also improves the power factor and reduces the harmonic distortions at the primary side of the transformer. The results obtained also suggest the existence of maximum power point or an optimum loading for the recovered harmonic power.